The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.17582/journal.pjz/20201225061228
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Cardiovascular Diseases

Abstract: Authors' Contributions SE conceived and designed the experiments. MÇ performed the experiments and analyzed the data. AA wrote the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Additionally, upon observing the binding modes of ACE2-SARS-CoV-2 S-protein in human and snake, three regions of snake ACE2 with large structural differences were observed. Within these regions, one compact yet complicated polar interaction network was formed between hACE2 and the S-protein of SARS-CoV-2, yet these polar contacts were not present in snake ACE2, which is the main reason for the reduced ability of snake ACE2 to bind SARS-CoV-2 [98][99][100][101][102]. Further to this, Luan et al [91] have generated structural simulations showing several key contacts of hACE2 with SARS-CoV-2 RBD and found that in snake ACE2, these contacts were completely eradicated.…”
Section: Snakementioning
confidence: 99%
“…Additionally, upon observing the binding modes of ACE2-SARS-CoV-2 S-protein in human and snake, three regions of snake ACE2 with large structural differences were observed. Within these regions, one compact yet complicated polar interaction network was formed between hACE2 and the S-protein of SARS-CoV-2, yet these polar contacts were not present in snake ACE2, which is the main reason for the reduced ability of snake ACE2 to bind SARS-CoV-2 [98][99][100][101][102]. Further to this, Luan et al [91] have generated structural simulations showing several key contacts of hACE2 with SARS-CoV-2 RBD and found that in snake ACE2, these contacts were completely eradicated.…”
Section: Snakementioning
confidence: 99%